PROTOTYPE ALAT MONITORING KESEHATAN PASIEN DAN PEMANGGIL PERAWAT BERBASIS INTERNET OF THINK (IOT) - Daniel, Rodo; Sukma, Shafril Muliawan; Yudhi, Yudhi; Faristasari, Evvin (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Nurse response systems rely heavily on the speed of information delivery and mobility. However, many hospitals still use wired call systems with static monitors, limiting mobility and delaying quick responses. This study designs an Internet of Things (IoT)-based nurse call system to monitor patient conditions in real-time and send notifications to nurses' smartphones via the Blynk application. The MAX30102 sensor is used to measure patients’ heart rate (BPM) and blood oxygen levels (SpO₂), while the RFID RC522 module records nurse presence. Test results show the system can accurately send notifications and log data, thus improving response time, efficiency, and the overall quality of nursing services.